Heterozygous Deletion of Chromosome 15q13.3 in a Boy with Developmental Regression, Global Developmental Delay, Hypotonia, and Short Stature - Allison M. Strauss; Anna C. Buhle; David M. Finkler (MDPI AG, 2022)
Two causes of intellectual disability are 15q13.3 deletion syndrome and BRWD3 X-linked intellectual disability. 15q13.3 deletion syndrome causes a heterogenous phenotype including intellectual disability (ID), developmental delay (DD), autism spectrum disorder, epilepsy/seizures, schizophrenia, attention deficit hyperactivity disorder, visual defects, hypotonia, and short stature. BRWD3 variants are rare, and the clinical presentation is largely unknown. Presented here is a 34-month-old male with developmental regression, global DD, hypotonia, and short stature. In this study, the patient and his mother underwent a whole-genome array screening. Sorting intolerant from tolerant (SIFT) and polymorphism phenotyping v2 (PolyPhen-2) analyses were performed to determine the pathogenicity of the BRWD3 mutation. Array comparative genomic hybridization showed a heterozygous, pathogenic deletion of at least 1.6 Mb from the cytogenetic band 15q13.2q13.3 and a BRWD3 variant of unknown clinical significance. This combination of genetic mutations has never been reported together and neither disorder is known to cause developmental regression. The mechanism of developmental regression is undefined but is of great importance due to the opportunity to develop therapies for these patients.